Education and human rights violation in Guyana - Samaroo, Noel K. (Institute of Latin American Studies, Texas University, 1990)
Education plays a central role in contemporary social development and change. The educational system in a given society assumes a major role in human development by making available to the individual the necessary equipment for interfacing with the network of social relations. In both developed and developing countries, education increasingly has been considered an essential individual right. The situation in Guyana illustrates the issue of human rights violation in education. There, despite the Compulsory Education Act of 1876, an entrenched plantation system obstructed the growth of mass education until after 1940. More recently, a deep and chronic economic crisis has forced a reduction in social spending in Guyana, particularly in the area of education. At the same time, the government has replaced meaningful instructional programmes with military training and mass games of dubious educational content in the interest of promoting ideological and propaganda goals. Guyana compares poorly with its Caribbean neighbours in academic achievement, and enrolment has fallen over time. Human rights violations exist in virtually every aspect of the Guyanese educational system. Malnutrition is severe among students and transportation to and from schools is lacking. In developing countries, and in Guyana in particular, where masses of people are engaged in the business of survival, there is little margin for contributing to the enrichment of society
Keywords: Educational development